INHIBISI EKSTRAK DAUN SIRIH MERAH TERHADAP LIPASE PANKREAS SEBAGAI ANTIOBESITAS SECARA IN SILICO - Mega Safithri; Nur Azizah; Maria Bintang; Rini Kurniasih (Jurnal Farmamedika (Pharmamedika Journal), 2023)
A Obesity triggers the emergence of various degenerative diseases, such as stroke, heart disease, type 2 diabetes, and insulin resistance. Pancreatic lipase inhibitors are anti-obesity drug agents that work by inhibiting pancreatic lipase enzymes. This study aims to search and predict the inhibitory activity of pancreatic lipase from the active compound of red betel leaf. The research began with virtual screening of 60 test ligands, prediction of ligand stability and toxicity, validation method of molecular docking, molecular docking, 2D and 3D visualization. The results showed that benzethonium octyloxyacetate, salicylic acid beta-D-glucopyranosyl ester, and anthocyanins had the best potential in inhibiting pancreatic lipase enzymes based on virtual screening, ligand stability, ligand toxicity, energy affinity, number of hydrogen bonds with active site, bond distance, and constants inhibition (Ki). Benzethonium octyloxyacetate has an affinity value of -8 kcal/mol, has a hydrogen bond interaction on the His349 residue on the active site of the pancreatic lipase receptor (6KSM) with a bond distance of 2,94 Å and Ki value of 1,347 μM.